2012
DOI: 10.1021/mp300081s
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Nanoparticle-Mediated Delivery of MicroRNA Inhibition and Alternative Splicing

Abstract: The crux of current RNA-based therapeutics relies on association of synthetic nucleic acids with cellular RNA targets. Antisense oligonucleotide binding to mature microRNA and splicing junctions on pre-mRNA represent methods of gene therapy that respectively inhibit microRNA-mediated gene regulation and induce alternative splicing. We have developed biodegradable polymer nanoparticles--which are coated with cell-penetrating peptides--that can effectively deliver chemically-modified oligonucleotide analogs to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 44 publications
1
66
0
Order By: Relevance
“…Another challenge in utilizing miRNAs as novel drug targets for PCa is developing antagonist and delivery system with high efficiency and specificity. Various types of chemically modified anti-miRs have been utilized to repress miRNAs, such as locked nucleic acid oligonucleotides (LNAs), polylysine-conjugated peptide nucleic acids (PNAs) and phosphorodiamidate morpholino oligomers (PMOs) [109][110][111][112]. However, because the cellular internalization of these hydrophobic, large anti-miRs is often ineffective, a more efficient delivery system needs to be developed.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge in utilizing miRNAs as novel drug targets for PCa is developing antagonist and delivery system with high efficiency and specificity. Various types of chemically modified anti-miRs have been utilized to repress miRNAs, such as locked nucleic acid oligonucleotides (LNAs), polylysine-conjugated peptide nucleic acids (PNAs) and phosphorodiamidate morpholino oligomers (PMOs) [109][110][111][112]. However, because the cellular internalization of these hydrophobic, large anti-miRs is often ineffective, a more efficient delivery system needs to be developed.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…However, because the cellular internalization of these hydrophobic, large anti-miRs is often ineffective, a more efficient delivery system needs to be developed. Some attempts have been made to enhance the cellular uptake of anti-miRs by conjugating the antisense oligonucleotides with cellpenetrating peptides (CPPs), such as Tat, Ant, MPG and more recently, Polymer nanoparticles (NPs) [109,113,114].…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…53 All the AMOs described until now were based on the modification on the ribose or nucleic acid backbone but other non natural nucleic acid analog such as phosphorodiamidate morpholino oligonucleotide (PMO) 54 and peptide nucleic acid can be employed to inhibit miRNAs. 14,[55][56][57][58] PNAs constitutes good alternative as they have high stability to both chemical and enzymatic degradation. 10 PNAs form very stable PNA:RNA duplexes, which can efficiently disrupt the dsRNA duplex.…”
Section: -45mentioning
confidence: 99%
“…Saltzman et al reported the use of (PLGA) polymer nanoparticles (100-200nm) coated with a nona-arginine (R9) cell penetrating peptide to deliver neutral anti-miRNAs (PNA and PMO) to inhibit miRNA-155. 57 The inhibition of miRNA-155 was monitored by a dual luciferase reporter system in which the target binding sequence for miRNA-155 was introduced at 3 0 UTR of Renilla Luciferase. KB cells transfected with this sensor system showed the inhibition of miRNA-155 transfected by anti-miRNA PNA and PMO.…”
Section: -45mentioning
confidence: 99%
See 1 more Smart Citation